(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Review of the terrorism development discovers not only the deep historical roots of the terrorism as a phenomenon, but also the terror’s dramatic role in the world history. Terrorism is the most effective accelerator of the destructive social processes, preparative and managerial starter of the planned social convulsions such as revolutions, rebellions, wars, ethnic conflicts, strategic communications seizure and elimination of competitors as well as induction of the religious and national discord. The acts of terrorism serve as a trigger for all the world and local wars which in their essence are nothing but the material wide-ranging form of ideologically religious, conceptual, political, ideological or weapon terrorism effected by the national socialized groups, states and political and military blocks. The thesis saying that the terrorism either anteceded to all the significant geopolitical events or accompanied them or turned to be their results is quite fair. Keywords: terror in history, development of terrorism, system of antiterror.